Effect of Siberian Light Crude Oil on Alfalfa (Medicago sativa L.) Cultivars - (Selcukcan) Erol, Cigdem; Ertekin, Ozlem; Unlu, Selma; Yildizhan, Yasemin; Onarici, Selma; Yuksel, Bayram; Memon, Abdulrezzak (Asian Journal of Chemistry, 2010)
The environmental petroleum contamination problem is getting increasingly important as the need for fertile land increases. Alfalfa (Medicago sativa L.) is a forage legume, which has uses in petroleum phytoremediation. In this study, three local cultivars of alfalfa from Eastern Anatolia were screened for their potential with respect to their for petroleum phytoremediation capacity and the effect of symbiotic nitrogen fixation of a symbiotic bacteria, Rhizobium meliloti, was evaluated. Local alfalfa cultivars; Savas, 1313 and 1312 were germinated and grown at soil mixed contaminated with different Siberian Light (SBL) crude oil concentrations for one month. Paralel studies were conducted with the application of R. meliloti. It could be said that the alfalfa cultivars are not very tolerant to the higher concentration of petroleum hydrocarbon contamination, but can only manage to grow on slightly contaminated areas.